2011
DOI: 10.1186/1742-2094-8-90
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease - a neurospirochetosis. Analysis of the evidence following Koch's and Hill's criteria

Abstract: It is established that chronic spirochetal infection can cause slowly progressive dementia, brain atrophy and amyloid deposition in late neurosyphilis. Recently it has been suggested that various types of spirochetes, in an analogous way to Treponema pallidum, could cause dementia and may be involved in the pathogenesis of Alzheimer's disease (AD). Here, we review all data available in the literature on the detection of spirochetes in AD and critically analyze the association and causal relationship between sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
289
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(311 citation statements)
references
References 161 publications
(255 reference statements)
7
289
0
15
Order By: Relevance
“…Both models (conventional and novel) were successfully established in the present study, and were shown to satisfy the Koch's criteria (Miklossy, 2011) for a causative relationship between a microbe and a disease: (1) The Acanthamoeba trophozoites or cysts were found either on the surface of the infected cornea or on the histochemical sections of infected corneas; (2) the clinical manifestations of typical keratitis caused by A. healyi infection were observed, including edema, opaque cornea, ulceration, abscess, and congestion; (3) the typical pathological features of keratitis were observed in the infected corneas, including inflammatory cells infiltration, neovascularization, and fibrosis; and (4) a strong immune response was observed with high antiAcanthamoeba IgG antibody titers, and elevated levels of total IgG, IgM, and INF-g in the sera of infected rabbits.…”
Section: Rabbit Model Of Acanthamoeba Keratitismentioning
confidence: 77%
“…Both models (conventional and novel) were successfully established in the present study, and were shown to satisfy the Koch's criteria (Miklossy, 2011) for a causative relationship between a microbe and a disease: (1) The Acanthamoeba trophozoites or cysts were found either on the surface of the infected cornea or on the histochemical sections of infected corneas; (2) the clinical manifestations of typical keratitis caused by A. healyi infection were observed, including edema, opaque cornea, ulceration, abscess, and congestion; (3) the typical pathological features of keratitis were observed in the infected corneas, including inflammatory cells infiltration, neovascularization, and fibrosis; and (4) a strong immune response was observed with high antiAcanthamoeba IgG antibody titers, and elevated levels of total IgG, IgM, and INF-g in the sera of infected rabbits.…”
Section: Rabbit Model Of Acanthamoeba Keratitismentioning
confidence: 77%
“…For this reason, we established a homemade indirect ELISA to measure the RL levels in CSF. The CSF samples of AD patients (21), MCI patients (13), and controls (7) were used. The CSF samples were taken from different individuals than those who provided the serum samples.…”
Section: The Elisa Methods For Rls Immunodetection In Csf From Ad Patimentioning
confidence: 99%
“…The surviving cells are able to expel strongly inflammatory components including LPSs [16]. The imputed role of pathogens in AD has been extensively reported for about over 200 different helical bacterial spirochete species [17], which may co-infect with other Gram-negative phylotypes [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have cultured and detected B. burgdorferi s.l. in the brains of psychiatric and Alzheimer's disease patients at autopsy [62][63][64][65][66][67]. Persistence of B. burgdorferi s.l.…”
Section: Neurological Manifestations Of B Burgdorferi Ssmentioning
confidence: 99%